Strengthening the Citizen-State Compact through Feedback : Effective Complaint Management as a Pathway to Articulate Citizen Voice and Improve State Response - World Bank (World Bank, Washington, DC, 2017)
The Palestinian Authority is committed to improving state-citizen relations through various mechanisms including the complaints resolution. The objective of this technical assistance, which has been undertaken at the request of the DGC, is to strengthen the Complaint Handling Mechanisms (CHMs) in five Palestinian ministries/government entities that are supported by World Bank-financed projects, as well as the DGC. This summary report synthesizes key findings that have emerged throughout the technical assistance and formulates Ministry-specific recommendations. It forms the basis of a possible phase II of the project, which would support the implementation of recommendations. The report presents the innovative methodology used to bring together the demand- and supply-side perspectives on CHMs in targeted ministries; the key findings from the survey and the ministry-by-ministry assessments; the key suggestions for improvement; and finally the next steps. The technical assistance has generated high client interest among the concerned Ministries, the DGC and development partners.The technical assistance has generated high client interest among the concerned Ministries, the DGC and development partners. This summary report synthesizes key findings that have emerged throughout the technical assistance and formulates Ministry-specific recommendations. It forms the basis of a possible phase II of the project which would support the implementation of recommendations. The technical assistance also aligns with the focus on strengthening the citizen-state compact specified in the WBG Assistance Strategy FY15-16 for the West Bank and Gaza. The report is structured as follows: Part two presents the context; Part three presents the methodology used to bring together the demand- and supply-side perspectives on CHMs in targeted ministries; Part four presents the key findings from the survey and the ministry-by-ministry assessments; Part five presents the key suggestions for improvement; and finally Part six presents the next steps.